COVID-19 Knowledge, Attitudes, and Preventive Measures of University Students in Bahrain - Perna, S.; Bahar, K.; Alalwan, T. A.; Zahid, M. N.; Gasparri, C.; Peroni, G.; Faragli, A.; La Porta, E.; Ali Redha, A.; Janahi, E. M.; Ibrahim, S.; Rondanelli, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The severe, acute respiratory syndrome COVID-19 that was first reported in China in December 2019 quickly became a global pandemic that has resulted in over 100 million infections and more than 2 million deaths. Study Design. This study aimed to assess the awareness level of university students regarding the possibility of becoming infected with COVID-19. In order to achieve this objective, we assessed the students’ knowledge, attitudes, and behaviors using an online survey questionnaire offered to a total of 300 students. Results. A positive response regarding awareness of COVID-19 symptoms was registered by more than 70% of the students, whereas 62% felt that wearing a mask did not give full protection against infection, approximately 30% agreed that antibiotics and antivirals did not treat COVID-19, and 62% agreed that vitamin C was helpful in treating common symptoms of COVID-19. Moreover, around 31% of the students believed that COVID-19 is a man-made virus. Students who had gotten infected with SARS-CoV-2 believed that wearing a mask gives full protection (p=0.018). In response to survey questions related to attitude, 80% of students cancelled and postponed meetings with friends, and 90% agreed that mask-wearing is the most precautionary measure used to prevent the infection. In addition, 82% avoided coughing in public, 82% avoided contact if they felt flu-like symptoms and 80% washed their hands far more often due to the pandemic. Interestingly, 76% carried hand sanitizer, 66.5% avoided shaking hands, and 42.7% were taking vitamin C supplements. Conclusions. This study showed that the participants had a positive awareness of COVID-19 transmission, symptoms, and treatments misconceptions and mistaken beliefs related to treatments and the origin of the virus were also common and should be addressed. This study thus provides a baseline for a population-based surveillance program that could help local authorities to improve pandemic preparation plans, particularly with regard to governmental education and media campaigns.